2021
DOI: 10.1016/j.quaint.2020.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Late Holocene Aleppo pine (Pinus halepensis Miller) woodlands in Mallorca (Balearic Islands, Western Mediterranean): Investigation of their distribution and the role of human management based on anthracological, dendro-anthracological and archaeopalynological data

Abstract: Late Holocene Aleppo pine (Pinus halepensis Miller) woodlands in Mallorca (Balearic Islands, Western Mediterranean): investigation of their distribution and the role of human management based on anthracological, dendro-anthracological and archaeopalynological data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…For instance, there was a predominant spatial pattern of aggregation in small patches showing facilitation rather than competition in plant communities, which would occur after a perturbation, far from density dependence and the carrying capacity of the system. Sparse data from 1921 and 1956 confirmed that, before the end of intense harvesting, vegetation showed an ecological state of a perturbed system, lacking forested patches and with 3.5-fold of lower plant diversity (see also Picornell-Gelabert et al, 2021). Vegetation cover increased more in flat than in step areas likely because the former were more impacted by anthropogenic activities and hold higher rat densities (Mayol et al, 2012).…”
Section: The End Of Long-term Harvesting By Humans For Vegetation Dyn...mentioning
confidence: 91%
See 1 more Smart Citation
“…For instance, there was a predominant spatial pattern of aggregation in small patches showing facilitation rather than competition in plant communities, which would occur after a perturbation, far from density dependence and the carrying capacity of the system. Sparse data from 1921 and 1956 confirmed that, before the end of intense harvesting, vegetation showed an ecological state of a perturbed system, lacking forested patches and with 3.5-fold of lower plant diversity (see also Picornell-Gelabert et al, 2021). Vegetation cover increased more in flat than in step areas likely because the former were more impacted by anthropogenic activities and hold higher rat densities (Mayol et al, 2012).…”
Section: The End Of Long-term Harvesting By Humans For Vegetation Dyn...mentioning
confidence: 91%
“…Harvesting of forests and grazing by free‐ranging domestic herbivores were synergetic with the abovementioned influence of climate change and determined a maquia‐type landscape, which shaped a new ecological state that has since then framed the dynamics of plant communities until recently. A new transition to a different state of vegetation dynamics is expected since the cessation of intense harvesting of natural resources, especially in small islands of the Balearic archipelago around the mid‐1970s (Carrión et al, 2010 ; Picornell‐Gelabert et al, 2021 ). Rural abandonment and the arrival of conservation laws a few years later allowed managers to protect these small ecosystems from new anthropogenic impacts, mainly habitat loss by touristic housing development.…”
Section: Introductionmentioning
confidence: 99%
“…Recent advances based on a systemic approach combining quantitative tools, anthraco-typology, particular growth patterns and anthraco-isotopy, have pushed back the limits of anthracology. This systemic approach applied to different archeological contexts enables easy reading between dendroanthracological parameters (Dufraisse and Coubray, 2018;Picornell-Gelabert et al, 2021). Interpretations of treering widths have been refined and hypotheses on the tree organs used have been proposed.…”
Section: Beyond Botanical Identification: Contribution Of Dendro-anth...mentioning
confidence: 99%
“…48 Beffa et al 2016;Aranbarri et al 2020;Tinner et al 2016;Morales- Molino et al 2021;Moser et al 2017. 49 Deckers 2016Picornell-Gelabert et al 2021. 50 Bintliff 2002Butzer 2005. …”
unclassified
“…55 D' Auria et al 2017Finkelstein & Langgut 2018; Langgut et al 2019 (overview article);Mercuri et al 2019b;Caracuta 2020;Galili et al 2021; Jouffroy-Bapicot et al 2021. 56 Fuel:Bouchaud et al 2017;D' Auria et al 2017;Janssen et al 2017;Marinova & Ntinou 2018;Picornell-Gelabert et al 2021. Water: Pustovoytov & Riehl 2016Enrich & Mejías 2017;Junge et al 2018;Meister et al 2018;Bruins et al 2019;Kaptijn & Ertsen 2019.…”
mentioning
confidence: 99%